Statistical analysis of masked data in a hybrid system based on copula theory under progressive hybrid censoring. Issue 2 (3rd April 2017) - Cai, Jing; Shi, Yimin; Bai, Xuchao
ABSTRACT: This article considers the reliability analysis of a hybrid system with dependent components, which are linked by a copula function. Based on Type I progressive hybrid censored and masked system lifetime data, we drive some probability results for the hybrid system and then the maximum likelihood estimates as well as the asymptotic confidence intervals and bootstrap confidence intervals of the unknown parameters are obtained. The effects of different dependence structures on the estimates of the parameter and the reliability function are investigated. Finally, Monte Carlo simulations are implemented to compare the performances of the estimates when the components are dependent with those when the components are independent.